The regional heterogeneity of wind power deployment: An empirical investigation of land-use policies in Germany and Sweden - Thomas Lauf; Kristina Ek; Erik Gawel; Paul Lehmann; Patrik Söderholm (Helmholtz-Zentrum für Umweltforschung (UFZ), 2018)
The purpose of this paper is to investigate the impacts of land-use policies on wind power deployment at the regional levels in Germany and Sweden, respectively. We use data on added wind capacity at the German district level and the Swedish municipality level over the time period 2008-2012. These data are analysed with a model specification permitting the probability of having any capacity addition (1/0) during this period to be independent of the level of the installed capacity (in MW). The results confirm that the regional variations in wind power deployment can to a significant extent be attributed to land-use policies, not least in the form of priority areas and the designation of restricted areas. The quantitative results display interesting differences across the two countries, not least concerning the role of priority areas, which is found to be much more profound in the German case. The assignment of protected areas appears instead to have constituted a more stringent policy tool in Sweden. Furthermore, cross-country differences in the relevance of various explanatory variables are also found to be related to geographical patterns, the overall extent of wind power deployment, as well as the design of the support schemes for wind power. Overall, the results highlight the need for better understanding of the critical role of land-use policies for future renewable energy development in various national and institutional contexts.
Keywords: 330; wind power; regional distribution; land-use policy; Germany; Sweden